Optimization of patient management during preimplantacionnoj genetic diagnosis - P A Bazanov; N G Mityushina; E V Yutkin; E Yu Voskoboeva (RUDN Journal of Medicine, 2013)
The article presents a study on optimization of patients who showed an preimplantacionnoj genetic diagnosis (PGD), identifying opportunities for expanding the range of indications for PGD, and show the validity of the PGD have fertile patients.